MORPHOTECTONIC ANALYSIS IN THE ELIKI FAULT ZONE (GULF OF CORINTH, GREECE) - Verrios, S.; Zygouri, V.; Kokkalas, S. (Bulletin of the Geological Society of Greece, 2004)
Morphotectonic analysis using geomorphic indices has been developed as a basic reconnaissance tool in order to identify areas experiencing rapid tectonic deformation or estimate relative variations of tectonic activity in a specific area. We applied this analysis in Eliki fault zone, which is located in the western part of the Gulf of Corinth. Eliki fault zone was selected because it displays a spectacular geomorphic expression and hosts historic and recent seismicity. The intensity of active tectonics is interpreted through a detailed geomorphic study of the fault-generated mountain fronts and fluvial systems. Tectonic geomorphology analysis of the Eliki footwall area includes the application of the most commonly used geomorphic indices, such as the mountain front sinuosity index (Smf), the valley floor / width ratio index (Vf), the stream gradient index (SL) and the transverse topographic symmetry factor (T). These indices were estimated on topographic maps and aerial photographs of the study area in order to correlate active tectonics and erosional processes. Our results imply that the Eliki fault zone can be assigned to a tectonic class of the higher tectonic activity. However, spatial variations of tectonic activity along the segmented studied fronts point to a general trend of increasing activity towards the east, which is gradually decreasing towards the west.